2008
DOI: 10.1007/s11273-008-9081-y
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation along hydrologic, edaphic, and geochemical gradients in a high-elevation poor fen in Canaan Valley, West Virginia

Abstract: Wetland plant community composition and pattern are regulated by a host of abiotic/environmental gradients and biotic factors. We used multivariate analyses to classify wetland plant communities and determine the relation of hydrologic, edaphic, and geochemical gradients on community composition and spatial distribution among 18 vegetation, hydrology, and soil sampling points in Abe Run, a botanically unique poor fen in northeastern West Virginia. We also examined the interactions of disturbance with the physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 29 publications
(35 reference statements)
1
15
0
Order By: Relevance
“…We believe the lack of significance can be contributed to the small number of locations where individual rare plants occurred, a problem inherent in sampling rare species (Steidl et al 1997). We believe our sampling protocols were adequate to pick up rare species in beaver ponds due to the combination of plot sampling and walk-around visual surveys (Poon and Margules 2004). Older ponds were found to harbor some rare plant species not found elsewhere in our study area.…”
Section: Discussionmentioning
confidence: 92%
“…We believe the lack of significance can be contributed to the small number of locations where individual rare plants occurred, a problem inherent in sampling rare species (Steidl et al 1997). We believe our sampling protocols were adequate to pick up rare species in beaver ponds due to the combination of plot sampling and walk-around visual surveys (Poon and Margules 2004). Older ponds were found to harbor some rare plant species not found elsewhere in our study area.…”
Section: Discussionmentioning
confidence: 92%
“…In addition to landowner permission or land acquisition, several surveys would need to be conducted before the sites were ready for mitigation. First, wetland hydrologic inputs would need to be determined by installing observation wells and monitoring them for at least 12 months (Rentch et al 2008). The water budget performed in Level 3 of this study gives an indication of the surface runoff to each site, but does not describe the groundwater or overbank flow of water to the site.…”
Section: Discussionmentioning
confidence: 99%
“…Determining hydrologic inputs to a potential wetland site is best conducted by installing observation wells and monitoring them for a year or more (Rentch et al 2008). Unfortunately, this option was not feasible because of time and logistical constraints.…”
Section: On-site Evaluation Survey-levelmentioning
confidence: 99%
“…High‐elevation wetlands in the central and southern Appalachian Mountains often support unique plant communities as well as rare or peripheral species (Stewart and Nilsen, 1993; Francl et al , 2004; Rentch et al , 2008). In headwater wetlands, vegetation composition may be highly variable over small spatial scales due to episodic inputs from ephemeral stream drainages or small changes in elevation (Francl et al , 2004; Rentch et al , 2008). Vegetative assessments have indicated that both small and large Appalachian wetlands are important for preservation of regional biodiversity as wetland size does not affect species richness or diversity (Francl et al , 2004).…”
Section: Introductionmentioning
confidence: 99%